Analisis Kemampuan Pemecahan Masalah Matematis Siswa Sekolah Menengah Pertama Pada Materi Persamaan Linear Satu Variabel - Iis Lestari; Eline Yanty Putri Nasution (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Students' mathematical problem-solving ability in the topic of linear equations in one variable (PLSV) is still not optimal because students tend to directly perform calculations or write final answers without going through systematic problem-solving steps. This study aims to describe students' mathematical problem-solving ability on the PLSV topic based on Polya's steps. This research uses a descriptive qualitative approach supported by simple quantitative data. The population of this study is eighth-grade students in a public junior high school in Sungai Penuh, with a sample of 16 students selected using purposive sampling. The research instrument is a mathematical problem-solving test consisting of five questions based on the indicators of understanding the problem, devising a plan, carrying out the plan, and checking the solution, and all items are declared valid. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that 18.75% of students are in the very good category, 6.25% in the good category, and 25% each in the fair, poor, and very poor categories. The highest indicator achievement is in carrying out the plan (89.06%), while the lowest is in devising a plan (29.68%). Therefore, students' mathematical problem-solving ability in the PLSV topic still needs to be improved, especially in habituating students to solve problems systematically according to Polya's steps.